Pengaruh Kebijakan Moneter, Makroprudensial dan Risiko Sistemik Terhadap Stabilitas Sistem Keuangan - Azaria, Disna Alvita (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
This study aims to analyze the effect of monetary and macroprudential policies issued by Bank Indonesia and systemic risk in banks on Financial System Stability in Indonesia. The variables used in this study are Non-Performing Loan, Statutory Reserves, BI Rate, Loan to Value, Capital Adequacy Ratio, and Return On Assets. The data is taken from the data provided by Bank Indonesia, OJK, etc. the data taken are monthly from 2012 to 2020. This study used the Ordinary Least Square (OLS) equation method which must fill up the Best Linear Unbiased Estimator (BLUE) assumption so that the results of the t-test and F-test are unbiased. The results of this study indicate that the relationship between Reserve and LTV on NPL is positive and not significant. Then the relation between BI Rate and ROA on NPL is negative and not significant and then the relation between CAR and NPL is positive and significant. Furthermore, the results of the study also show that together monetary policy, macroprudential policy, and systemic risk affect up to 95% of changes on NPL in Indonesia.